Coastal management 2019 : joining forces to shape our future coasts - Hardiman, Nick (ICE Publishing, 2020)
The Institution of Civil Engineers' Coastal Management conference series is the leading forum for the presentation of the latest developments in coastal engineering. The 9th conference took place in La Rochelle, France, from 24-26 September 2019. The proceedings of this conference, Coastal Management: Joining forces to shape our future coasts, comprises 45 peer-reviewed papers from the conference that present current issues, international research and practical applications.
Also issued in print: 2020.
Conference proceedings.
Keywords: Coastal engineering -- Congresses.; Coastal zone management -- Congresses.; elektronické knihy; electronic books